An innovative cardiopulmonary resuscitation mannequin for common people - Putri, Runi Pramesti; Endiyono, Endiyono (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2020)
Background: The success of basic life support is determined by the role of the individual(s) who first encountered a patient with a heart attack, and he will be a helper in the situation. Lack of socialization and training for laypeople makes them unable to implement a right first aid in cases of cardiac arrest. There is a need for innovations in cardiac, pulmonary resuscitation for ordinary people to facilitate them in practicing compression measures. Technic: CPR mannequin is made of a plywood material in the shape of the human body; it is 34 cm long, 34 cm wide, and 6.5 cm high. There are 2 LED lights to detect the accuracy of the compression depth. Conclusion: CPR mannequin can facilitate and improve the skills of laypeople in performing cardiopulmonary resuscitation